Economic reliability of the organisation in the context of groups of interests of the business environment - D. A. Borisyuk; O. E. Astafyeva (Управление)
An important aspect of the interaction of the subjects of legal relations is the process of making a management decision on the possibility of partnership. This makes it necessary to assess the economic reliability of a participant in the relationship, both a potential partner and within the framework of the interaction that took place. The purpose of the article is to show a variety of approaches when analysing the organisation economic reliability. The approach proposed to assessing the organisation reliability from the point of view of the goals of different interest groups of the organisation business environment has been illustrated. The object of the study is the concept of the organisation economic reliability. The subject of the study is the differences between the goals (markers) of different interest groups in assessing the organisation economic reliability. The methodological and theoretical basis of the research is general and private scientific approaches to studying the essence of the definition and methods of assessing the organisation economic reliability. The article is based on the system approach methodology. During the study the methods of comparative analysis, the method of expert assessments, normative and logical methods were used. In addition, CyberLeninka, eLibrary.Ru, Scopus, Web of Science, and Google Scholar were used as academic citation database. To ensure the accuracy of the literature review process, all publications were studied independently by the authors. The article reveals the dependence of the assessment and the form of presentation of the results of the assessment of the organisation economic reliability on the group of users in whose interests it is carried out.